O Conjunto Urbano Lagoinha, Bonfim e Carlos Prates: conflitos entre conservação e renovação no âmbito do planejamento urbano - Brenda Melo Bernardes (2023)
Located outside the limits of Avenida do Contorno, in the central region of Belo Horizonte (former suburban area), the neighborhoods Lagoinha, Bonfim and Carlos Prates have their process of occupation linked to the construction period of Belo Horizonte, which defines peculiar aspects concerning the urban layout and in the establishment of symbolic references and representative buildings of the municipal heritage. However, despite the importance carried out by these neighborhoods as creators of the collective memory of the capital, they lack investments from the public authorities to improve urban infrastructure according to the demands of their residents and initiatives that contribute to the preservation and maintenance of their cultural references. Nevertheless, the Lagoinha Region, which comprises the neighborhoods of Bonfim, Lagoinha and part of Carlos Prates, has been facing the divergence of preservation and renovation interests manifested in the urban policy: on one side represented by the will in maintaining its heritage importance through the institution of Conjunto Urbano Lagoinha, Bonfim and Carlos Prates (Deliberation No. 193/2016) and, on the other side, by the proposal of the Operação Urbana Consorciada Antônio Carlos/Pedro I – Leste-Oeste (OUC ACLO) and its unfoldings through the presentation of the Plano de Qualificação Urbanística Centro-Lagoinha (2021). Therefore, considering the perimeter of Conjunto Urbano Lagoinha, Bonfim, and Carlos Prates as a spatial cutout, the thesis aims to understand how heritage protection guidelines can instigate conflicting interests with other urban policy guidelines in Belo Horizonte. It is investigated as a research hypothesis that there is an interest conflict of planning between the protection and urban renewal guidelines recommended for the region comprising the Conjunto Urbano Lagoinha, Bonfim and Carlos Prates. The proposed research, which is qualitative, includes documentary, field, and bibliographic research, as well as semi-structured interviews to inform the discussions related to the neighborhoods. The researched period is from 2014, when the proposal for the Operação Urbana Consorciada Antônio Carlos/Pedro I – Leste-Oeste was released, covering the period of the institution of Conjunto Urbano Lagoinha, Bonfim and Carlos Prates (2016), up to the current context, given the promulgation of the Plano Urbanístico da Operação Urbana Centro-Lagoinha, released in 2021.